Transformations of citral over bifunctional Ru-H-Y-80 extrudates in a continuous reactor - Vajglová Zuzana; Navas Marisa; Mäki-Arvela Päivi; Eränen Kari; Kumar Narendra; Peurla Markus; Murzin Dmitry Y. (Elsevier B.V., 2025)
One-pot transformations of citral were investigated over Ru-catalysts in a batch and a continuous mode over a powder catalyst and extrudates, respectively. Ru/H-Y-80 catalysts were prepared by different impregnation methods to obtain different particle sizes of Ru.
The highest yield of isopulegols was 15% and yield of menthols was 3% with stereoselectivity to the desired (±)-menthol isomer of 42% after 5 h over the Ru/H-Y-80 powder catalyst with the smallest metal particles prepared by the incipient wetness impregnation method with six impregnation steps using Ru(NO)(NO3)3 as a precursor. This catalyst was synthesized with the Bindzil binder and shaped by extrusion.
For comparison, also a catalyst with Ru deposited on the binder was prepared. Addition of 30 wt% Bindzil binder to Ru/H-Y-80 catalyst caused significant catalyst deactivation. Z/E-citral ratio decreased with increasing Ru particle size. Citral conversion and the yield of acyclic hydrogenation products were higher over the powder catalysts containing a mixture of zeolite and binder with a larger distance between the metal and the acid sites, i.e. with Ru deposited on the Bindzil binder. Long-term experiments in the continuous mode revealed comparable catalytic behaviour of both Ru-extrudates with the controlled metal location due to the presence of diffusion regime. The maximum yield of menthols, 6%, with stereoselectivity to the desired (±)-menthol of 73% was obtained during the transient state, below 2 h of time-on-stream. The reuse of Ru/H-Y-80 extrudates was successfully demonstrated.